The Application of PMA (Propidium Monoazide) to Different Target Sequence Lengths of Zebrafish eDNA: A New Approach Aimed Toward Improving Environmental DNA Ecology and Biological Surveillance - Hirohara, Takaya; Tsuri, Kenji; Miyagawa, Koichi; Paine, Robert T. R.; Yamanaka, Hiroki (Frontiers in Ecology and Evolution, 2021)
Environmental DNA (eDNA) analysis has enabled more sensitive and efficient biological monitoring than traditional methods. However, since the target species is not directly observed, interpretation of results cannot preclude process Type I errors. Specifically, there may be a spatial or temporal gap between the target eDNA and the eDNA source in the sampled area. Moreover, eDNA surveillance lacks the ability to distinguish whether eDNA originated from a living or non-living source. This kind of Type I error is difficult to control for, in part, because the relationship between the state of eDNA (i.e., intracellular or extracellular) and the degradation rate is still unclear. Here, we applied PMA (Propidium monoazide) to eDNA analysis which enables us to differentiate “intact cells” from “disrupted cells”. PMA is a dye that has a high affinity for double stranded DNA and forms a covalent bond with double-stranded DNA and inhibits amplification of the bonded DNA molecules by PCR. Since PMA is impermeable to the cell membrane, DNA protected by an intact cell membrane can be selectively detected. In this study, we investigated the workability of PMA on vertebrate eDNA using zebrafish, Danio rerio. Aquarium water was incubated for one week to monitor the eDNA degradation process of both intracellular and extracellular eDNA. We developed ten species-specific quantitative PCR assays for D. rerio with different amplification lengths that enabled independent quantification of total eDNA (sum of intracellular and extracellular eDNA, commonly measured in other studies) and intracellular eDNA (DNA in intact cells) and allow for analyses of sequence length-dependent eDNA degradation in combination with PMA. We confirmed that PMA is effective at differentiating “intact” and “disrupted” fish cells. We found that total eDNA and intracellular eDNA have different degradation processes that are dependent on the length of target sequence. For future conservation efforts using eDNA analyses, it is necessary to increase the reliability of the analysis results. The research presented here provides new analysis tools that expand our understanding of the ecology of eDNA, so that more accurate and reliable conclusions can be determined.